THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND AGGRESSIVE BEHAVIOR IN ADOLESCENTS AT SMK X SIDOARJO - Chusnul Widya; Mariyati, Lely Ika (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to determine This study quantitatively explores the relationship between emotional intelligence and aggressive behavior correlation with insynthetic techniques. Method: The variable in this study is emotional intelligence towards aggressive behavior. The sample in this study amounted to 289 vocational students determined based on the table of Issacc and Michael with a level of 5%. The hypothesis of this study is that there is a negative association between emotional intelligence and aggressive behavior. Results: The results of the study obtained were proven to have a negative relationship between emotional intelligence and aggressive behavior, namely the significance value of emotional intelligence to aggressive behavior of 0.012 which means 0.012 < 0.05 with an rxy value of -0.133 (negatively correlated). This means that the higher the emotional intelligence, the lower the aggressive behavior. Conversely, the lower the emotional intelligence of the meal the higher the aggressive behavior. Novelty: This research was motivated by the phenomenon in adolescents at SMK